Effects of Substrate Temperature on Vacuum Deposited Thin Film of Disperse Red 1 on ITO Glass - H. Taunaumang; Herman Herman; M. O. Tjia (Journal of Mathematical and Fundamental Sciences, 2001)
Abstract. Highly crystalline thin films of photorefractive Disperse Red 1 (DR 1) molecule have been fabricated on clean substrate of ITO (indium tin oxide) glass by means of physical vapor deposition at various substrate temperatures. In addition to molecular orientation and organization revealed by their XRD and FTIR spectral characteristic and the enhancement of those effects by substrate temperature, further analysis of FTIR spectrum around nitrobenzene absorption band indicates the formation of strong hydrogen bond resulting in a head-tail stacking of the molecules. The deposited films also show systematic reduction of light absorption in the visible region with increasing substrate temperature. This modification of the optical property is clearly favorable for long wavelength photonic applications of DR1 film. Pengaruh Suhu Substrat pada Film Tipis 'Disperse Red 1' yang Dideposisi pada Gelas ITO dalam VakumSari. Dalam eksperimen ini telah berhasil diperoleh melalui proses deposisi vakum sejumlah film tipis bahan fotorefraktif dari molekul "Disperse Red 1" (DR1) dengan krisalinitas tinggi di atas substrat gelas ITO ("indium tin oxide") pada berbagai suhu. Selain efek orientasi dan organisasi molekul yang ditunjukkan oleh karakteristik spectra XRD dan FTIR bersangkutan serta peningkatan efek tersebut dengan suhu substrat, analisis lebih lanjut dari data FTIR di sekitar pita absorpsi nitrobenzene telah mengungkapkan tanda embentukan ikatan hydrogen yang kuat yang menghasilkan susunan "head-tail" yang bertumpuk. Film yang terdeposisi juga memperkihatkan pengurangan absorpsi cahaya secara sistematik di daerah tampak, seiring dengan peningkatan suhu substrat. Perubahan sifat optik ini jelas bermanfaat bagi aplikasi film DR1 untuk devais fotonik dalam daerah gelombang panjang.